EGFR and HER3 signaling blockade in invasive mucinous lung adenocarcinoma harboring an NRG1 fusion. (October 2018) - Kim, Hye Sook; Han, Ji-Youn; Shin, Dong Hoon; Lim, Kun Young; Lee, Geon Kook; Kim, Jin Young; Jacob, Wolfgang; Ceppi, M.; Weisser, Martin; James, I.
Highlights: Invasive mucinous adenocarcinoma of the lung (IMA) lacks effective therapeutic target. NRG1 fusions have been reported in 8–27% of IMA. NRG1 fusion upregulates HER-PI3K-AKT pathway. First reported cases of IMA with NRG1 fusion treated with HER3 and EGFR blockade. Abstract: Rearrangements of NRG1 have been identified in invasive mucinous adenocarcinoma of the lung (IMA), formerly referred to as mucinous bronchioloalveolar carcinoma. NRG1 ligand signals through induction of HER2-HER3 heterodimers, thus leading to PI3K–AKT pathway activation. Therefore, targeting HER2, HER3 and the downstream pathway may be a hypothesis-driven strategy for IMA with NRG1 fusion. Herein we reported two patients who benefited from lumretuzumab, a monoclonal anti-HER3 antibody, in combination of erlotinib during a clinical trial (NCT01482377). At least sixteen weeks of progression-free survival were achieved without any unacceptable toxicity.